2015
DOI: 10.1159/000373995
|View full text |Cite
|
Sign up to set email alerts
|

MiR-429 Determines Poor Outcome and Inhibits Pancreatic Ductal Adenocarcinoma Growth by Targeting TBK1

Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) ranks fourth on the list of cancer-related causes of death and its prognosis has not improved significantly over the past decades. Deregulation or dysfunction of miRNAs contribute to cancer development. Previous data indicates that miR-429 is involved in the pathogenesis of PDAC. However, the role of miR-429 in PDAC remained unknown. Methods: MiR-429 levels in sample tissues of 78 patients and in PANC1 and SW1990 cell lines were quantified by real-time PCR. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…By contrast, miR-429 may act as a tumor suppressor in certain cancer types. Song et al (22) reported that miR-429 was frequently downregulated in pancreatic ductal adenocarcinoma (PDAC) tissues and cell lines, and lower miR-429 expression in PDAC tissues significantly correlated with shorter survival of PDAC patients. In addition, overexpression of miR-429 inhibited PDAC cell growth via targeting TANK-binding kinase 1 (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, miR-429 may act as a tumor suppressor in certain cancer types. Song et al (22) reported that miR-429 was frequently downregulated in pancreatic ductal adenocarcinoma (PDAC) tissues and cell lines, and lower miR-429 expression in PDAC tissues significantly correlated with shorter survival of PDAC patients. In addition, overexpression of miR-429 inhibited PDAC cell growth via targeting TANK-binding kinase 1 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Song et al (22) reported that miR-429 was frequently downregulated in pancreatic ductal adenocarcinoma (PDAC) tissues and cell lines, and lower miR-429 expression in PDAC tissues significantly correlated with shorter survival of PDAC patients. In addition, overexpression of miR-429 inhibited PDAC cell growth via targeting TANK-binding kinase 1 (22). Ye et al (23) reported that miR-429 inhibited the migration and invasion of breast cancer cells via inhibition of zinc finger E-box binding homeobox 1 and Crk-like expression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the improvement gained from medical advance, PDAC remains one of the highest mortality rates, and very low survival improvements have been made, a rate essentially unchanged over the course of the years [3,4]. Additionally, nearly 80% of patients who present with locally advanced or metastatic diseases have an extremely poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has implicated miRNAs as essential regulators of atherosclerosis by targeting key factors in the regulatory pathways [3,23,24]. Specifically, miR-429 has been reporter as a tumor suppressor in various cancers [25][26][27][28][29][30][31][32][33]. Moreover, the role of miR-429 in carcinogenesis has been associated with apoptosis augmentation [34,35].…”
Section: Introductionmentioning
confidence: 99%